Desenvolvimento do projeto gráfico para um livro ilustrado de contos infantis - Andreatta, Helena Franco (2014)
This project has as objective the creation of an illustrated children's fairy tales book. Through a theoretical survey regarding the genre's appearance and importance were determined the functions of these narratives and how they were adapted to transmitting values to the reader. The factors which differenciate fairy tales from myths and fables have been analyzed with the purpose of determining which stories can compose the book. Therefore, the narratives with the same theme have been selected: the moral development of the wolf. The paper of the graphic choices and how they alter the initial perception of the reader have been discussed. alongside the comunicative capacity of the illustration. It has been determined which is the age group of the children that like fairy tales and which is the best approach to creating a book for it. The pop up was pointed out as the resource which most interests this age, so mechanisms used in this technic were studied.